Islamic AI Literacy as Responsible Knowledge Practice: Development and Validation of AILS-IIUS in Indonesian Islamic Higher Education - St. Syamsudduha; Suwandi Suwandi; Tabrani ZA (Jurnal Pendidikan Islam, 2026)
Artificial intelligence (AI) integration in higher education has increased the need for context-sensitive AI literacy frameworks aligned with ethical and educational values. This study aimed to develop and validate the Artificial Intelligence Literacy Scale for Indonesian Islamic University Students (AILS-IIUS) within the framework of Islamic AI literacy. Grounded in the principles of adab, amanah, ‘adl, maslahah, and tabayyun, the study conceptualized AI literacy through four dimensions: Awareness, Usage, Evaluation, and Ethics. Using a quantitative scale-development design, data were collected from 361 undergraduate students enrolled at Islamic higher education institutions in Indonesia. Furthermore, the instrument development process involved expert validation, contextual refinement, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and regression analysis. Additionally, the findings produced a valid 15-item instrument explaining 72.38% of the total variance. The four-factor model demonstrated satisfactory model fit, reliability, convergent validity, and discriminant validity. Furthermore, the frequency of AI use significantly predicted all dimensions of AI literacy. Based on these results, the study concludes that AI literacy in Islamic higher education should incorporate conceptual understanding, evaluative judgment, ethical engagement, and responsible AI-supported learning. Ultimately, the AILS-IIUS provides an Islamically grounded framework to support ethical AI pedagogy and curriculum development in Islamic higher education.